The Emerging (Social) Neuroscience of SES. Issue 8 (August 2016) - Varnum, Michael E. W.
Abstract: Social scientists have long been interested in understanding how socioeconomic status (SES) affects the way people think, feel, and behave. Neuroscience has provided new tools (fMRI, EEG, and ERP) to allow us to answer these questions, demonstrating, for example, that lower SES is linked to stronger mirror neural responses, greater mentalizing, enhanced vigilance to threat, and lesser likelihood to spontaneously infer traits based on limited information. The present paper (i) reviews evidence that SES affects neural responses involved in a wide range of psychological processes, (ii) highlights the value of neural methods in investigations of SES, (iii) discusses cultural neuroscience as a potential framework to understand why SES has the effects it does on the brain, (iv) considers previous developmental neuroscience findings regarding SES and attention in light of cultural neuroscience, and (v) discusses future challenges, opportunities, and questions for this emerging field.